Differential damage and repair of DNA-adducts induced by anti-cancer drug cisplatin across mouse organs - Askar Yimit; Ogun Adebali; Aziz Sancar; Yuchao Jiang (Nature Communications, 2019)
Cisplatin, a platinum chemotherapeutic agent, is widely used to treat several cancers. Here Yimit et al. revert to genome-wide approaches to map and analyze cisplatin damage formation and excision repair with single nucleotide resolution across different mice organs following platinum treatment.